Organization of Eastern Caribbean States Systematic Regional Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
Eastern Caribbean countries are among the region’s top performers in per capita income, poverty reduction, access to services, and gender inclusion, despite the constraints imposed by their small size. Geography and economic specialization make them vulnerable to external shocks, contributing to low and volatile GDP growth since 2000. High debt, limited job opportunities, and climate change present important development challenges for OECS countries. Strengthening their resilience to shocks is a prerequisite for poverty reduction, inclusive growth, and sustainability. The natural capital of the oceans provides opportunities for OECS countries to embed growth in the “blue economy.” Realizing these opportunities will require harnessing human capital, embracing new technologies, and continued regional cooperation.